Evaluation of Tumor DNA Sequencing Results in Patients with Gastric and Gastroesophageal Junction Adenocarcinoma Stratified by TP53 Mutation Status. (26th February 2022) - Wood, Anthony C; Zhang, Yonghong; Mo, Qianxing; Cen, Ling; Fontaine, Jacques; Hoffe, Sarah E; Frakes, Jessica; Dineen, Sean P; Pimiento, Jose M; Walko, Christine M; Mehta, Rutika
Abstract: Background: Gastric cancer (GC) and gastroesophageal junction adenocarcinomas (GEJ) are molecularly diverse. TP53 is the most frequently altered gene with approximately 50% of patients harboring mutations. This qualitative study describes the distinct genomic alterations in GCs and GEJs stratified by TP53 mutation status. Patients and Methods: Tumor DNA sequencing results of 324 genes from 3741 patients with GC and GEJ were obtained from Foundation Medicine. Association between gene mutation frequency and TP53 mutation status was examined using Fisher's exact test. Functional gene groupings representing molecular pathways suggested to be differentially mutated in TP53 wild-type ( TP53 WT ) and TP53 mutant ( TP53 MUT ) tumors were identified. The association of the frequency of tumors containing a gene mutation in the molecular pathways of interest and TP53 mutation status was assessed using Fisher's exact test with a P -value of <.01 deemed statistically significant for all analyses. Results: TP53 mutations were noted in 61.6% of 2946 GCs and 81.4% of 795 GEJs ( P < .001). Forty-nine genes had statistically different mutation frequencies in TP53 WT vs. TP53 MUT patients. TP53 WT tumors more likely had mutations related to DNA mismatch repair, homologous recombination repair, DNA and histone methylation, Wnt/B-catenin, PI3K/Akt/mTOR, and chromatin remodeling complexes. TP53 MUT tumors more likely had mutations related to fibroblast growth factor, epidermal growth factor receptor, other receptor tyrosine kinases, and cyclin and cyclin-dependent kinases. Conclusion: The mutational profiles of GCs and GEJs varied according to TP53 mutation status. These mutational differences can be used when designing future studies assessing the predictive ability of TP53 mutation status when targeting differentially affected molecular pathways. Abstract : Gastric (GC) and gastroesophageal junction adenocarcinomas (GEJ) are molecularly diverse. TP53 is the most frequently altered gene, with approximately 50% of patients harboring mutations. This article describes the distinct genomic alterations in GCs and GEJs stratified by TP53 mutation status.